Interleukin-1 Receptor Antagonist Protects Newborn Mice Against Pulmonary Hypertension - Bui, Christine B.; Kolodziej, Magdalena; Lamanna, Emma; Elgass, Kirstin; Sehgal, Arvind; Rudloff, Ina; Schwenke, Daryl O.; Tsuchimochi, Hirotsugu; Kroon, Maurice A. G. M.; Cho, Steven X.; Maksimenko, Anton; Cholewa, Marian; et al. (Frontiers in Immunology, 2019)
Pulmonary hypertension secondary to bronchopulmonary dysplasia (BPD-PH) represents a major complication of BPD in extremely preterm infants for which there are currently no safe and effective interventions. The abundance of interleukin-1 (IL-1) is strongly correlated with the severity and long-term outcome of BPD infants and we have previously shown that IL-1 receptor antagonist (IL-1Ra) protects against murine BPD; therefore, we hypothesized that IL 1Ra may also be effective against BPD-PH. We employed daily injections of IL-1Ra in a murine model in which BPD/BPD-PH was induced by antenatal LPS and postnatal hyperoxia of 65% O2. Pups reared in hyperoxia for 28 d exhibited a BPD-PH-like disease accompanied by significant changes in pulmonary vascular morphology: micro-CT revealed an 84% reduction in small vessels (4-5 µm diameter) compared to room air controls; this change was prevented by IL-1Ra. Pulmonary vascular resistance, assessed at d28 of life by echocardiography using the inversely-related surrogate marker time-to-peak-velocity/right ventricular ejection time (TPV/RVET), increased in hyperoxic mice (0.27 compared to 0.32 in air controls) and fell significantly with daily IL-1Ra treatment (0.31). Importantly, in vivo cine-angiography revealed that this protection afforded by IL-1Ra treatment for 28 d is maintained at d60 of life. Despite an increased abundance of mediators of pulmonary angiogenesis in d5 lung lysates, namely vascular endothelial growth factor (VEGF) and endothelin-1 (ET-1), no difference was detected in ex vivo pulmonary vascular reactivity between air and hyperoxia mice as measured in precision cut lung slices, or by immunohistochemistry in alpha-smooth muscle actin (α-SMA) and endothelin receptor type-A (ETA) at d28. Further, on d28 of life we observed cardiac fibrosis by Sirius Red staining, which was accompanied by an increase in mRNA expression of galectin-3 and CCL2 (chemokine (C-C motif) ligand 2) in whole hearts of hyperoxic pups, which improved with IL-1Ra. In summary, our findings suggest that daily administration of the anti-inflammatory IL-1Ra prevents the increase in pulmonary vascular resistance and the pulmonary dysangiogenesis of murine BPD-PH, thus pointing to IL-1Ra as a promising candidate for the treatment of both BPD and BPD-PH.